Cordyceps sinensis (yarsagumba): Pharmacological properties of a mushroom - Sanjukta Sen; Dipanjan Karati; Rosy Priyadarshini; Tarun Kumar Dua; Paramita Paul; Ranabir Sahu; Gouranga Nandi (Elsevier, 2023)
Introduction: Yarsagumba (Cordyceps sinensis or Ophiocordyceps sinensis) is a fungus that parasitizes ghost moth larvae and produces a fruiting body prized as herbal medicine, belonging to the Ophiocordycipitaceae family. Cordyceps species are also known as traditional Chinese medicine (TCM) as it has wide applications in the pharmaceutical and health sectors. For thousands of years, Yarsagumba has been recognized in Nepal. It is one of the world's most promising medicinal mushrooms. Its unusual life cycle and wide range of medical applications piqued scientists' curiosity throughout the previous three decades. The purpose of this review is to compile information on Yarsagumba, including its history, cultivation, taxonomic characteristics, and many therapeutic uses, as well as phytochemical and pharmacological studies completed to date. Methods: Different sources and distribution of the fungus have been presented along with its life cycle, morphology, collection procedure, and history as traditional Chinese medicine. Various chemical constituents of the fungus have been presented in tabular form with their significance as nutrients and traditional medicine. Various pharmacological activities have also been presented in tabular form with their mechanism of action, which include antiasthmatic, antineoplastic, antibacterial, aphrodisiac, cardioprotective, anti-cancer, immunomodulator, etc. Different adulteration methods and standardization approaches have also been summarized. Results: This review summarizes various aspects of yarsagumba relevant to its uses as traditional Chinese medicine. Conclusion: Despite its scientific advancement, further research is needed, particularly in the design of dosage forms and analysis that will lead to the most effective use of this most expensive medicinal fungus.